Analisis Perilaku Penggunaan Kredit Digital dan Dampaknya terhadap Kesehatan Keuangan Konsumen: Studi pada Mahasiswa Pengguna ShopeePay Later - Ayu Rahayu; Enik Rahayu (Journal of Education, Humaniora and Social Sciences (JEHSS), 2026)
This article aims to analyze the behavior of digital credit usage through ShopeePay Later and its impact on the financial health of university students in Semarang Regency. The problem focuses on how usage intensity, consumption motives, perceived ease of use, and the management of digital credit repayment obligations influence students’ financial conditions. To address this issue, the study draws on theories of financial behavior and consumer financial health. This research employs a qualitative approach with a case study design. Data were collected through in-depth interviews with purposively selected student users of ShopeePay Later, supported by limited observation and relevant documentation, and were analyzed qualitatively using thematic analysis. The findings indicate that the use of ShopeePay Later among students is driven by perceived ease of access, payment flexibility, and digital promotional features, which tend to encourage short-term and consumptive spending patterns. Intensive and poorly controlled use negatively affects students’ financial health, as reflected in difficulties managing debt, reduced saving capacity, and weakened short-term financial stability. However, the selective use of digital credit that is aligned with financial capability does not necessarily result in negative outcomes. This study concludes that the impact of digital credit on students’ financial health is largely determined by user behavior, particularly self-control, financial planning, and awareness of digital debt risks.